A distinct gap in gendered impact of girls education empowerment on family wellbeing in rural Katsina, Northern Nigeria - Abdullahi, Ibrahim; Zainalaludin, Zumilah; Paim, Laily (2013)
Despite practical experience on female teachers being a role model in rural schools and voluminous literature on the important of females education, and their roles as integral part of nation’s citizen, it appeared that still female intellectual potential and asset were being ignored and perceived negatively by most men. This study contrasts the findings to discovered different perception and feeling between male and female respondents on the impacts of girls’ education on their wellbeing through quantitative research. Four hundred structured questionnaires were distributed randomly on the equal basis among males and females to examine elements of education empowerment and the element economic wellbeing. The analysis of the study reveals that female respondents express positive feeling with positive correlation on the impacts of girl education empowerment on their wellbeing than their men counterpart. It also shows significant relationship (p<.005) in the wellbeing of female respondents, no significant relationship (p>.005) in with men economic wellbeing. This study see it mandatory to suggest that government at all levels in Nigeria should developed gender sensitive education plan and adhere to its implementation. Strong advocacy is recommended with support of religious and community leaders in the rural areas. This study as part of growing body of knowledge, and contribute toward future studies on similar subject matter.